Investigation of Liner Systems in Transport of Organic and Inorganic Contaminants in Sanitary Landfill: A Case Study. Issue 1 (18th November 2016) - Varank, Gamze; Demir, Ahmet; Adar, Elanur; Bilgili, Mehmet Sinan; Top, Selin; Yazici Guvenc, Senem; Ozcoban, Mehmet Sukru
Abstract : In the present work, a pilot‐scale study was carried out to investigate the diffusive transport of phenolic compounds and advective transport of heavy metals through liner systems composed of alternative materials and to evaluate the leachate effect on liner materials' properties. For this purpose, ten pilot‐scale landfill reactors were operated for a period of about 290 days. Physico‐chemical, mineralogical composition, and geotechnical properties of liner materials were also reported. The results of the study suggest that performance of alternative liner systems have no significant difference in toxic organic contaminant attenuation and clay‐lime mixture were found to be the less effected liner system by leachate. Thereby clay‐lime mixtures can be effectively utilized as a component of landfill liners due to not only chemical, physical, and mineralogical properties but also their high abundance and low cost supply. A two‐layer liner system composed of clay‐lime mixture at the upper part and bentonite‐zeolite mixture at the lower part is recommended. Existence of lime at the upper part will provide improvement in soil properties and reduce leachate effects but will increase hydraulic conductivity by decreasing the thickness of diffuse double layer. A bentonite‐zeolite mixture existing at the lower part will provide adsorption of heavy metals and avoid heavy metal migration. Abstract : A pilot scale study is carried out to investigate migration of phenolic compounds and heavy metals from landfill leachate to groundwater using alternative liner systems. The results show that liner systems had no significant effect on the migration of phenolic compounds but transport of heavy metals had been prevented by adsorption and precipitation processes occuring in liner systems.